Potato - Carolina Lizana, X.; Sandaña, Patricio; Behn, Anita; Ávila-Valdés, Andrea; Ramírez, David A.; Soratto, Rogério P. [UNESP]; Campos, Hugo (Elsevier, 2020)
Potato is one of the main food crops and is widely adapted to diverse environments worldwide. Although the genetic origin of the current improved potatoes is relatively narrow, physiological traits, nutritional traits, and resistance to diseases vary widely. Furthermore, native potatoes are a rich source of genes that can be useful in genetic improvement. Potato is frost-and drought-sensitive, with a limited root system. Although these environmental factors can severely reduce yield, potato is plastic and can partially compensate, yield components. Actual farm yield ranges from 5t of fresh tubers per hectare (median yield in Uganda) to 124t of fresh tubers per hectare (Columbian Basin, US), and the yield gap ranges from 10% to 75%. The yield gap of potato is high in developing countries, where availability of inputs and crop management constrain actual yield. In high-input systems, the main challenges for sustainable production include reliance on pesticides and management of fertilisers and irrigation to increasing the efficiency in the use of resource use and reducing environmental impacts. The potato, especially the native germplasm, has superior nutritional and health properties that could be exploited in new varieties with wider consumption. The challenges of food security in a context of climate change in potato production systems require innovative management (e.g. intercropping), improving the efficiency in the use of resources, chiefly water and nitrogen, and new products and storage technologies.
Keywords: Breeding; Management; Potato; Quality; Solanum tuberosum spp. L.; Yield